2022
DOI: 10.1111/cns.13925
|View full text |Cite
|
Sign up to set email alerts
|

Determination of significant parameters in remote ischemic postconditioning for ischemic stroke in experimental models: A systematic review and meta‐analysis study

Abstract: Objectives:To systematically review studies using remote ischemia postconditioning (RIPostC) for ischemic stroke in experimental models and obtain factors that significantly influence treatment outcomes. Materials and Methods:Peer-reviewed studies were identified and selected based on the eligibility criteria, followed by extraction of data on potentially influential factors related to model preparation, postconditioning, and measure time based on outcome measures including infarct size, neurological scales, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…According to our studies, it is suggested that chronic RIC is a good option for patients who are not eligible for the narrow window for thrombolysis (within 4.5 h after symptom onset) and endovascular reconstruction (within 24 h after symptom onset based on two studies published online on Oct 13, 2022, in the New England Journal of Medicine, 5,8 ) and our result was consistent with most preclinical meta-analyses. 20,21,23,24 However, one study 23 performed within 48-72 h showed better effects compared with those performed in the hyperacute stage and 4-7 days. Given the limited evidence, the exact time window and the most effective neuroprotective RIC intervention period could not be fully determined.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…According to our studies, it is suggested that chronic RIC is a good option for patients who are not eligible for the narrow window for thrombolysis (within 4.5 h after symptom onset) and endovascular reconstruction (within 24 h after symptom onset based on two studies published online on Oct 13, 2022, in the New England Journal of Medicine, 5,8 ) and our result was consistent with most preclinical meta-analyses. 20,21,23,24 However, one study 23 performed within 48-72 h showed better effects compared with those performed in the hyperacute stage and 4-7 days. Given the limited evidence, the exact time window and the most effective neuroprotective RIC intervention period could not be fully determined.…”
Section: Discussionmentioning
confidence: 92%
“…Although there have been previous systematic reviews and meta‐analyses of RIC as a neuroprotective therapy, most of them focused on preclinical animal models 20–24 . However, translating treatment effects on stroke from animal ischemia models to clinical reality is often a great challenge due to nonphysiological experimental conditions in animals that do not reflect human conditions 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In exploring English-language databases, only four meta-analyses and systematic reviews relevant to this field have been identified, with two focusing on animal studies and the other on clinical trials. The reviews of animal studies [ 84 , 85 ], though encompassing a wide array of primary research and conducted across various species, provided a comprehensive and detailed assessment of the outcomes. These analyses present robust evidence supporting the preclinical efficacy of RIPostC.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic postconditioning (IPO) is a treatment method for I/R injury. The core of IPO is to mitigate reperfusion injury through short, alternating blood flow blockade and restoration during the reperfusion stage [ 105 ]. Research has shown that IPO can effectively protect intestinal I/R injury from ischemic postconditioning by inducing autophagy, activating Akt, inactivating GSK-3β, and activating Nrf2.…”
Section: Programmed and Non-programmed Cell Deathmentioning
confidence: 99%